To Know the Indigenous Other: A Century of Indians in Canadian History - Downey, Allan (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2023)
Celebrating its centenary in 2022, the Journal of the Canadian Historical Association (JCHA) has been home to scores of articles on Indigenous history within the colonial borders of Canada. Offering a historiography of the past one-hundred years of scholarship appearing in the journal focused on Indigenous topics, this article argues that the JCHA offers a unique case study of the history of the field. While the journal has offered a dearth of scholarship on people of colour, leading to the erasure of Black Canadians as prominent actors in Canada’s past, the zealous study of “Indians” within the journal’s pages is salient. However, much like the larger field of Canadian history, the journal has a fraught and contentious past with Indigenous Peoples, stories, and methods. Unlike the erasure of Black Canadians, the fervent focus on “Indians” in Canadian history has had the significant effect of Canadians coming to “know” the Indians who were produced within the power structures of Canadian imperialism, settler colonialism, and the academy as they sought to identify, classify, and organize the Other. More recently however, there has been a slow trickle of articles produced by historians of Indigenous history that is contributing to an intellectual sovereignty that situates Indigenous history as an independent and unique course of study not tied exclusively or directly to the nation-states of the United States and Canada.